Professionalization of Public Health in Nepal - Khatri, Rose (Europasian Journal of Medical Sciences, 2020)
Background: The need for a professionalized and highly skilled public health workforce is essential to improving and protecting the health of populations, especially in Nepal. This study aimed to explore: (i) the current trends in public health in Nepal and (ii) the opportunities and barriers to the professionalization of the sector. Methods: We employed an exploratory qualitative research design and used a combination of semi-structured interviews with senior public health professionals and a small focus group discussion with more recently qualified public health practitioners in Nepal. A total of nine professional stakeholders were interviewed and five junior practitioners joined the focus group discussion. Data was collected via Skype due to COVID-19 restrictions. Thematic analysis was used to analyze the data. Results: Four core themes emerged from the research: understanding the public health approach; health priorities; federalization and the impact on public health practice; professionalization and workforce development. Conclusions: Political federalization and more recently COVID-19 have impacted the development, capacity, and employment of this often-neglected workforce. Public health graduates with their broad-ranging knowledge and skills are often overlooked in the health sector. This is related to a general lack of understanding of what public health is and what public health practitioners do amongst politicians and the general public.